KAJIAN KELAYAKAN MODEL PEMBANGUNAN HUTAN TANAMAN RAKYAT POLA MANDIRI BERBASIS AGROFORESTRI - Djohar Efendi (Lambung Mangkurat University-Indonesia, 2016)
The analysis about the financial advisability of agroforestry-based, autonomous HTR development was done using the concept of “present worth” or “present value” by using investment index or criteria: Net Present Value (NPV), Internal Rate of Return (ORR), and Gross Benefit Cost Ratio (Gross BCR). The values of NPV, BCR dan IRR calculated using interest rate of 15% for 30 consecutive years of cultivation starting from the largest were as follows: 1) Jabon & corn: NPV = Rp. 103.564.000 -, BCR = 2,11 dan IRR= 50,57 %, 2) Rubber, jabon & corn: NPV = Rp. 73.669.000,-, BCR =1,63 dan IRR = 47,16 %, 3) Rubber & corn: NPV = Rp. 43.773.000,-, BCR = 1,31 dan IRR = 34,75 %, 4) Rubber, mahogany & corn: NPV = Rp.26.348.000,-, BCR = 1,23 dan IRR = 31,25%, and 5) Mahogany & corn: NPV = Rp. 8.924.000,-, BCR = 1,11 dan IRR = 17,45%. Financially, using interest rate of 15% and within 30 years of cultivation, the implementation of agroforestry-based, autonomous HTR development with the plants combinations of rubber & corn; mahogany & corn; rubber, jabon & corn; and rubber, mahogany & corn, is advisable to improve the income of the farmers. Kajian mengenai kelayakan finansial pembangunan HTR pola mandiri berbasis agroforestri, dianalisis dengan menggunakan konsep